Implementation of Village Fund Management in Tatengesan Village, Pusomaen District, Southeast Minahasa Regency - Mary Vanye Sandag (Journal of Social Science, 2021)
This study uses a qualitative research type, primary data collected through interview techniques, observation and supported by secondary data, namely documentation. The data analysis of this research used an interactive model consisting of “data collection, data display, data condensation, concluding; drawing and verifying” developed by Miles, Huberman, and Saldana. The results of this study prove that the management of the Village Fund for the 2019 fiscal year is in the planning stage, seen from the musrembang held by the Village Fund implementation team that is still less effective, wherein the musrembang activity community participation is still very low, due to the lack of transparency of information conveyed by the Tatengesan Village apparatus to the community. Tatengesan Village. Implementation based on research results is less effective, the use of the Village Fund budget can be resolved properly but due to the lack of transparency of information related to the implementation of activity planning by the village government to the community, so that the achievement of the objectives of the Village Fund management carried out in Tatengesan Village is still less effective. Accountability in the Village Fund Management process in improving physical development in Tatengesan Village is still less effective, the preparation of the accountability report only focuses on one person, namely the Operator. There is no evaluation of activities that should be carried out with the Tatengesan Village community and the capacity of human resources is still inadequate. Lack of information obtained by the community from the village government so that the community does not know at all their function as a direct supervisory team in the management of the Village Fund, but the community only knows that there is and has been the implementation of development in the village.